How Does a Whistleblowing System Prevent Earnings Management? Insights from Corporate Governance Perspective - Giovani, Cut Maneka; Anzib, Nuraini; Arfan, Muhammad (Indatu Journal of Management and Accounting, 2024)
The whistleblowing system (WBS) is a component of the internal control system that plays a crucial role in preventing irregularities and fraud, as well as reinforcing the implementation of good governance practices. Therefore, this study aims to examine the whistleblowing system's role in moderating the effect of corporate governance (institutional ownership, independent commissioners, and audit committees) on earnings management. The population of this study comprises 147 manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the period from 2017 to 2021. The sample was selected using simple random sampling, resulting in 60 companies per year and a total data observation of 300. Moderated Regression Analysis (MRA) was chosen as the analysis method, and the estimation results indicate that the whistleblowing system strengthens the negative effect of institutional ownership, independent commissioners, and audit committees on earnings management. These results demonstrate that with a whistleblowing system in place, governance functions more effectively in reducing earnings management compared to companies without such a system. This study contributes to the literature by illustrating that the whistleblowing system operates more optimally with the support of corporate governance. Policies are needed to enhance the relationship between corporate governance mechanisms and earnings management activities, with the whistleblowing system policy expected to enhance the effectiveness of functional governance and consequently reduce earnings management activities.